Environmental management strategies for urban solid waste (MSW) in the Tacna region, 2010. - Zegarra Alvarado, Noribal Jorge (2014)
Objective: Evaluate management strategies of municipal solid waste (MSW) and its impact on the conservation of the environment and ecosystem of the region of Tacna, 2010. Method: The work is for applied research, as the knowledge and the experience to solve a critical problem oriented, using the participatory methodology that allowed a dynamic multidisciplinary working, with representatives of district municipalities, of the provincial municipality, regional government, using a methodological guide. The sample was collected in the months of April to June 2010; this information was compiled using standard formats, previously designed for this purpose. Result: The data that were obtained were tabulated and presented in tables and graphs, so that the management strategies of municipal solid waste (MSW) and its impact on the conservation of the environment and ecosystem of the region of Tacna was evaluated, 2010. Conclusions: The integrated management of municipal solid waste is the best way to tackle the problems arising from production and uncontrolled dumping of the same because, unchecked, directly or indirectly discharge reduces the quality of community life and damages environment.